1991
DOI: 10.1042/bst0190385
|View full text |Cite
|
Sign up to set email alerts
|

Nerve-growth-factor-treated and v-src-expressing PC 12 cells: a model for neuronal differentiation

Abstract: Arachidonic acid (20:4) is liberated from membrane phospholipids by the action of phospholipase A, (PLA,). One pathway of metabolism is the oxygenation by membrane-bound cyclo-oxygenase to form prostaglandin (PG) endoperoxides. They are either isomerized to PGD,, PGE, and PGF,, or are substrates for thromboxane and prostacyclin synthase. Other arachidonic acid (20:4) metabolizing enzymes are cytosolic lipoxygenases which catalyse the incorporation of one oxygen molecule into 20:4 at the 5-, 12-, or 15-position. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…For example, infection of avian myoblasts, retinoblasts, or chondroblasts with RSV maintains these cells in a proliferative state and blocks differentiation into myotubes, neuroretinal cells, epidermal cells, or chondrocytes, respectively (Muto et al 1977, Yoshimura et al 1981, Crisanti-Combes et al 1982, Alema & Tato 1987. In contrast, introduction of v-Src into PC12 cells or immature sympathetic neurons induces neurite outgrowth and terminal differentiation into neuron-like cells (Alema et al 1985, Haltmeier & Rohrer 1990, Hecker et al 1991. As discussed previously, these dramatic alterations in cell differentiation induced by v-Src do not imply that cellular Src mediates these effects when activated under natural conditions.…”
Section: Differentiationmentioning
confidence: 99%
“…For example, infection of avian myoblasts, retinoblasts, or chondroblasts with RSV maintains these cells in a proliferative state and blocks differentiation into myotubes, neuroretinal cells, epidermal cells, or chondrocytes, respectively (Muto et al 1977, Yoshimura et al 1981, Crisanti-Combes et al 1982, Alema & Tato 1987. In contrast, introduction of v-Src into PC12 cells or immature sympathetic neurons induces neurite outgrowth and terminal differentiation into neuron-like cells (Alema et al 1985, Haltmeier & Rohrer 1990, Hecker et al 1991. As discussed previously, these dramatic alterations in cell differentiation induced by v-Src do not imply that cellular Src mediates these effects when activated under natural conditions.…”
Section: Differentiationmentioning
confidence: 99%
“…These protein kinases can be activated by a variety of extracellular signals, and interact with multiple intracellular substrates, including focal adhesion kinase (FAK) 1 , p130Cas, structural proteins such as cortactin, and connexin 43, and stimulate other signaling pathways within the cell. Src family kinases have been linked to cellular events such as cell adhesion, cytoskeletal rearrangements, cell migration, regulation of the cell cycle, apoptosis, and differentiation ( Boschek et al, 1981 ; Hecker et al, 1991 ; Twamley-Stein et al, 1993 ; Kaplan et al, 1995 ; Rodier et al, 1995 ; Huang et al, 1997 ).…”
mentioning
confidence: 99%
“…A possible role of Src in myoblasts, retinoblasts and chondrocytes differentiation was demonstrated using v‐Src (Muto et al 1977; Yoshimura et al 1981; Crisanti‐Combes et al 1982; Alema & Tato, 1987). Fyn and Lyn were implicated in osteoclast differentiation (Kaabeche et al 2004), while v‐Src promotes PC12 differentiation into neurone‐like cells (Alema et al 1985; Haltmeier & Rohrer, 1990; Hecker et al 1991). Therefore, we evaluated the expression of Src in trophoblasts and its activation after FBS addition, a factor known to induce trophoblast differentiation (Daoud et al 2005 a ).…”
Section: Discussionmentioning
confidence: 99%
“…Kaabeche et al (2004) showed that degradation of Fyn and Lyn, induced by constitutive fibroblast growth factor receptor‐2 activation, supported osteoblast differentiation. In contrast, introduction of v‐Src into PC12 cells or immature neurones induced neurite outgrowth and terminal differentiation into neurone‐like cells (Alema et al 1985; Haltmeier & Rohrer, 1990; Hecker et al 1991). Furthermore, c‐Src was implicated in human trophoblast differentiation (Rebut‐Bonneton et al 1993), while Src, Yes and Lyn were activated during rat trophoblast giant cell differentiation (Kamei et al 1997).…”
mentioning
confidence: 94%